Character Actualization of Hard Work - Syapal, Zulkarnain; Amin, Alfauzan (LPPM Undiksha, 2022)
Character education should bring students to the introduction of cognitive values, appreciation of affective values, and absolute value experiences. However, the problem that often occurs is that some students have poor character. This study aims to analyze the character of hard work owned by students and the obstacles experienced in the realization of challenging work character education in schools. The method used in this study is a mixed-method. The sample used in this study amounted to 80 samples with a purposive sampling technique. The methods used in collecting data are observation, interviews, and questionnaires. The data collection instrument used a questionnaire sheet. The technique used to analyze the data is qualitative and quantitative analysis techniques. The study's results, namely the character of students' hard work, found that students had an average complex work character with good categories. Although at first, the educators admitted that they experienced obstacles such as laziness, boredom, and a sense of wanting to give up experienced by students. However, this can be overcome by providing support and motivation by educators in learning.